Art education development in the context of global changes - Yefimenko, Iryna V.; Yakymchuk, Olena M.; Kravtsova, Nataliia Ye.; Sotska, Halyna I.; Korol, Anatolii M. (Linguistics and Culture Review, 2021)
New trends are emerging in the system of higher art education due to globalisation and integration, rapid development of technological innovations. The use of technological innovations causes emerging of new types of communication, collaboration and interaction between teachers and students. In the article, the concept of smart education and its principles and the competence of a future teacher and specifics of their professional training were described. Global educational trends were characterised. The perspectives of professional and pedagogical activity of art teacher were outlined. The importance of technological innovations in the process of innovative education was explained. The criteria for assessing the teacher’s innovative competence were highlighted. It was established that the modern smart society requires a teacher who teaches art history while constantly developing his cognitive abilities, systematically renew his intellectual and creative potential. The peculiarities of teacher’s innovative competence formation in the changing conditions of a modern “smart” society were investigated. It was concluded that digital competence is one of the new requirements for art critics training in the context of the development of the information-oriented society.